Is fruit and vegetable intake associated with asthma or chronic rhino-sinusitis in European adults? Results from the Global Allergy and Asthma Network of Excellence (GA2LEN) Survey. Issue 1 (December 2017) - Garcia-Larsen, Vanessa; Arthur, Rhonda; Potts, James; Howarth, Peter; Ahlström, Matti; Haahtela, Tari; Loureiro, Carlos; Bom, Ana; Brożek, Grzegorz; Makowska, Joanna; Kowalski, Marek; Thilsing, Trine; et al.
Abstract Background Fruits and vegetables are rich in compounds with proposed antioxidant, anti-allergic and anti-inflammatory properties, which could contribute to reduce the prevalence of asthma and allergic diseases. Objective We investigated the association between asthma, and chronic rhino-sinusitis (CRS) with intake of fruits and vegetables in European adults. Methods A stratified random sample was drawn from the Global Allergy and Asthma Network of Excellence (GA2 LEN) screening survey, in which 55, 000 adults aged 15–75 answered a questionnaire on respiratory symptoms. Asthma score (derived from self-reported asthma symptoms) and CRS were the outcomes of interest. Dietary intake of 22 subgroups of fruits and vegetables was ascertained using the internationally validated GA2 LEN Food Frequency Questionnaire. Adjusted associations were examined with negative binomial and multiple regressions. Simes procedure was used to control for multiple testing. Results A total of 3206 individuals had valid data on asthma and dietary exposures of interest. 22.8% reported having at least 1 asthma symptom (asthma score ≥1), whilst 19.5% had CRS. After adjustment for potential confounders, asthma score was negatively associated with intake of dried fruits (β-coefficient −2.34; 95% confidence interval [CI] −4.09, −0.59), whilst CRS was statistically negatively associated with total intake of fruits (OR 0.73; 95% CI 0.55, 0.97). Conversely, a positive association was observed between asthma score andalliums vegetables (adjusted β-coefficient 0.23; 95% CI 0.06, 0.40). None of these associations remained statistically significant after controlling for multiple testing. Conclusion and clinical relevance There was no consistent evidence for an association of asthma or CRS with fruit and vegetable intake in this representative sample of European adults.